2015
DOI: 10.1017/s1478951515000747
|View full text |Cite
|
Sign up to set email alerts
|

A new measure of home care patients' dignity at the end of life: The Palliative Patients' Dignity Scale (PPDS)

Abstract: The new PPDS has appropriate psychometric properties that, together with its briefness, encourages its applicability for dignity assessment at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
0
25
0
4
Order By: Relevance
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to language, eleven studies analyzed were published in Portuguese (9)(10)(11)(18)(19)(20)(21)(23)(24)(25)(26) and from Brazilian authors, five were published in Spanish (12)(13)(15)(16)(17) and three in English (14,16,22) . Of the included studies, eight (9)(10)(11)(17)(18)(19)(20)(21) used the qualitative approach and ten, the quantitative (12)(13)(14)(15)(16)(22)(23)(24)(25)(26) . As for the instruments / techniques for data collection/production, questionnaires, interviews, observation, discussion groups and application of scales were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several measures exist which were originally intended to measure HRQOL, but these measures were either developed for use in other diseases such as cancer, (e.g., revised Hospice Quality of Life Index [13]; Death and Dying Distress Scale [14; 15]; McGill Quality of Life Questionnaire [16; 17]; QUAL-EC [18]) or are overly generic (e.g., CANHELP Lite [19]; EOL-PRO [20]; the Missoula-VITAS quality of life index [21]; Palliative Patients’ Dignity Scale [22]; Patient Needs Assessment in Palliative Care [23]; Valuation of Life [24]; QUAL-E [25]). These tools do not capture EOL concerns specific to HD (e.g., concerns related to watching other family members suffer from and die from the disease; concerns about the burden of having HD places on other family members; concerns about your children inheriting the disease from you; the fact that there is a gene test that can accurately predict who will get symptoms, but not when), take too long to implement (i.e., the CANHELP [26]), and/or include substandard psychometric properties [6-8].…”
mentioning
confidence: 99%